Rational Use of Medicines in Community Pharmacies in the Ledzokuku-Krowor Municipality - Opong, B.Y. (University of Ghana, 2016)
Rational use of medicines (RUM) for all medical conditions is an essential element in achieving quality of health and medical care for patients. Yet more than 50% of all medicines worldwide are prescribed, dispensed or sold inappropriately. Ensuring the availability, affordability and rational use of quality medicines is an issue of concern in developing countries. Irrational drug use affects quality of health care and access and exerts undue financial burden on the health care system and on patients and increases morbidity and mortality and has implications for resistance to antiinfectives. Community Pharmacies by their ease of access and high patronage serve as a vital source of information on drug usage to members of the community and should promote the safe use of drugs. The main objective of this study was to assess rational use of quality and accessible medicines in community pharmacies in the Ledzokuku-Krowor municipality using WHO level II facility core based indicators. A descriptive cross-sectional design employing the quantitative method was employed to take prospective data from 6 community pharmacies and 180 clients using pre –tested structured questionnaires. Majority (53.3%) of the patients for whom medicines were intended for were females whilst those aged 30- 59 years were in the majority (46.7%). About 98.8 % of clients travelled to the community pharmacy in < 1hour and at a cost 0.42 times the daily wage of the lowest paid salaried government worker. Availability of key essential medicines was high (92.2%) and no expired medicine was found in any of the dispensaries. These medicines were conserved under conditions that scored 80%. The Median Price Ratio (MPR) of all the surveyed medicines ranged from 0.13 to 26.11implying that medicines were being sold at a range 0.13 times lower and 26.11 times higher than the international reference price. As much as 60.83% of prescription medicines were bought without prescriptions. Labelling of medicines in the municipality was low -58.9% although 88.2% of them had adequate knowledge on how to take their medicines. The average cost of medicines bought was 0.73 times the daily wage of the lowest paid salaried government worker. In general, the level of the rational use of medicines in community pharmacies was found to be good, although there were some major sub optimal performance regarding some patient care practices.
Thesis(MPH)-University of Ghana, 2016
Keywords: Rational Use; Medicines; Community Pharmacies; Ledzokuku-Krowor Municipality